ANALISIS HASIL HIBRIDISASI TANAMAN JAGUNG (Zea Mays Saccharata) Dan JAGUNG KETAN (Zea Mays Ceratina) MENGGUNAKAN METODE PERSILANGAN BUATAN: ANALYSIS OF HYBRIDIZATION RESULTS OF CORN (Zea Mays Saccharata) and CORN PLANT (Zea Mays Ceratina) USING MADE CROSSING METHOD - Saputra, Johan Adi (Jurnal Ilmiah Rhizobia, 2020)
To support large-scal e corn exports by the Minister of Agriculture, production is needed. One way is by hybridizing corn plants to produce new corn plants with high production. This study aims to determine the results of crosses between sweet corn and sticky corn. Reinforcement Sidoarjo with a height of sea level Â± 7m in May to August 2018. This research was carried out descriptively with 2 types of crosses of sweet corn as female parent and glutinous corn as male parent (TK) and glutinous corn as female parent and sweet corn a s male parent (KT), which is repeated 4 times then continued with unpaired T Test and the usual percentage to determine the difference between TK and K The variables observed were ear weight, seed color, seed shape, and dry weight per 100 seeds. The resu lts showed that crosses gave rise to 3 color variants namely white, yellowish white and yellow. With a color ratio of 3: 1 in the TK treatment and 1: 3 in the KT treatment. Crosses of sweet corn and sticky corn also produced 2 different forms of corn, namely wrinkles and solid forms with a total percentage of 16,625% in the form of wrinkles and 83,375% in round shape. Â  Â